2008
DOI: 10.3844/ajabssp.2008.627.632
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Chemical and Sensory Attributes of Solar and Freeze-Dried Jameed Produced from Cow and Sheep Milk with the Addition of Carrageenan Mix to the Jameed Paste

Abstract: Jameed is a fermented dried dairy product in the form of stone hard balls or other shapes produced by straining the heated buttermilk on cloth mesh bags, salting the formed paste by kneading, shaping and drying in the sun. This product is reconstituted after disintegration to be used in the preparation of Mansaf, the national dish in Jordan, which is basically lamb meat cooked in Jameed sauce (Sharab, Mareece) and served on cooked rice. The addition of Carrageenan (0.15%), to the Jameed paste resulted in impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…It has been reported that the addition of 1% starch, 0.15% carrageenan and 1% wheat flour may enhance the solubility, physical, cohesion and consistency properties of jameed after drying (Mazahreh et al . ; Hasbani ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the addition of 1% starch, 0.15% carrageenan and 1% wheat flour may enhance the solubility, physical, cohesion and consistency properties of jameed after drying (Mazahreh et al . ; Hasbani ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, Klila has never been seriously studied and only few microbiological, biochemical and technological data are available (Benamara and Megaiz, 1998;Leksir and Chemmam, 2015). On the contrary, Jameed, a similar Middle-East cheese or Chhana a cheese made in India, are well characterized (Mazahreh et al, 2008). These studies laid the groundwork for the development of specific technologies such as atomization or lyophilisation to produce these traditional cheeses at the industrial scale.…”
mentioning
confidence: 99%
“…Whipping of the paste to which Carrageenan was added resulted in further improvement to solubility and the stability of dispersion (Mazahreh et al . ) . Industrial spray‐dried ‘jameed’ had a lower moisture content than the traditional sun‐dried product, dispersibility was higher and average particle size was smaller, but wettability, bulk density and colour were comparable between the two products (Shaker et al .…”
Section: Traditional Milk Processing and Derived Productsmentioning
confidence: 97%
“…In one set of experiments, the addition of 0.15% Carrageenan to the 'jameed' paste resulted in improvement as evaluated by wettability and synaeresis test of solar-dried jameed. Whipping of the paste to which Carrageenan was added resulted in further improvement to solubility and the stability of dispersion (Mazahreh et al 2008). 4 Industrial spray-dried 'jameed' had a lower moisture content than the traditional sun-dried product, dispersibility was higher and average particle size was smaller, but wettability, bulk density and colour were comparable between the two products (Shaker et al 1999).…”
Section: Jordanmentioning
confidence: 99%